Localized In Vivo Electro Gene Therapy (LiveGT)-Mediated Skeletal Muscle Protein Factory Reprogramming - Jacob Hensley; Michael Francis; Alex Otten; Nadezhda Korostyleva; Tina Gagliardo; Anna Bulysheva (Applied Sciences)
Gene electrotransfer (GET) has gained significant momentum as a non-viral gene delivery method for various clinical applications, primarily in the cancer immunotherapy and vaccine development space. Preclinical studies have demonstrated exogenous gene delivery and expression in various tissues, including the liver, skin, cardiac muscle, and skeletal muscle. However, protein replacement applications of this technology have yet to be fully actuated. Plasmid DNA skeletal muscle delivery has been shown to maintain expression for up to 18 months. In the current study, we evaluated localized skeletal muscle delivery for protein replacement applications. We developed localized in vivo electro gene therapy (liveGT) protocols utilizing mono- and biphasic pulse sequences for localized pulse delivery directly to skeletal muscle with a custom monopolar platinum electrode. Plasmid DNA encoding human insulin and human glucokinase were chosen for this study to evaluate the liveGT platform for protein replacement potential. Initial in vitro GET was performed in mouse myoblasts to evaluate human insulin and glucokinase co-delivery. This was followed by liveGT-mediated reporter gene delivery in the skeletal muscle of Sprague–Dawley rats for pulse sequence selection. Protein replacement potential was evaluated in healthy (non-diabetic) rats with liveGT-mediated human insulin and glucokinase co-delivery to skeletal muscle. Human and rat insulin levels were measured via ELISA over the course of 3 months. Fed-state blood glucose measurements were monitored in correlation with serum human insulin levels. LiveGT-mediated skeletal muscle reprogramming successfully produced physiological levels of human insulin in serum over the course of 3 months. Hypo- and hyperglycemic events were not observed. Therefore, liveGT is a safe and viable platform for potential protein replacement therapies.